Transition Guide Dissemination to Foster Patient–Care Team Conversations: A Childhood Arthritis Rheumatology Research Alliance Transition Learning Collaborative Pilot Implementation Study - Joyce C. Chang; Gabrielle Alonzi; Cora Sears; Nicole Bitencourt; Alex Hernandez; Rosemary Peterson; Risa Alperin; Rebecca S. Overbury; Mariel dela Paz; Lindsay N. Waqar‐Cowles; Patience H. White; Kristine Carandang; et al. (ACR Open Rheumatology)
Objective Uptake of evidence‐informed health care transition processes among pediatric rheumatologists is low despite poor outcomes of transition from pediatric to adult care. We piloted a learning collaborative model to implement transition guides. We dually assessed implementation outcomes and changes in reported patient–care team discussions about transition. Methods This was a type II hybrid effectiveness‐implementation pilot study of transition guide dissemination to patients at least 14 years old with rheumatic conditions across nine pediatric rheumatology centers in the Childhood Arthritis Rheumatology Research Alliance Transition Learning Collaborative. We evaluated implementation outcomes (feasibility, adaptations, and fidelity) and the proportion of patients surveyed that reported having discussions with their care team regarding transfer planning. Results Six sites were retained through the COVID‐19 pandemic (below 70% target). Five out of six sites contributed outcome data (met 80% target) but with substantial heterogeneity in how transition guides were shared (eg, in‐person, electronic messages, and posted flyers), and data were collected. The pooled proportion of respondents having discussed transfer planning with their care team was 39% preimplementation (n = 239; 95% confidence interval [CI] 32%–46%) and 55% postimplementation (n = 864; 95% CI 36%–73%). After implementation, there were significant increases in the likelihood of respondents recalling receiving a transition guide (odds ratio [OR] 2.58, 95% CI 1.35–4.92) and discussing transfer planning (OR 2.14, 95% CI 1.30–3.52), adjusted for age and site of care. Conclusion Transition guide dissemination is a simple intervention associated with increased awareness among young people with rheumatic conditions and discussions with their care team about transition preparation. The learning collaborative model facilitated identification of several dissemination strategies adaptable to site‐specific resources.